USING VIRTUAL REALITY IN ENGINEERING GRAPHICS EDUCATION (Neo Scientific Peer Reviewed Journal, 2026)
This in research engineering graphics using virtual reality (VR) technologies in education use through students spatial his/her thinking develop issue studied . Traditional education methods often three dimensional objects complete to understand enough opportunity Virtual reality and 3D models for students with real time in mode work opportunity giver interactive the environment presented Research during supreme education institution students in the presence of experience lessons was held and VR technologies training to the process current Results this showed that , based on VR education received students spatial imagination and mastery level according to traditional in a way to those who read relatively high to the results achieved . Research in the end, VR technologies engineering graphics education efficiency noticeable at the level increase proved.